KAJIAN DOSIS PUPUK KANDANG AYAM DAN FREKUENSI PENYIRAMAN TERHADAP PERTUMBUHAN BIBIT SENGON (Paraserianthes falcataria (L) Nielson) - sigit wijayanto; dewi ratna nurhayati; Efrain Patola (Innofarm:Jurnal Inovasi Pertanian, 2019)
The  purpose of  this research was to study : (1) interaction effect between the dosage of chicken manure with the frequency of  watering, (2) effect  of  chicken  manure  dosage,  and (3)  effect of watering frequency, to the growth of sengon seedlings. This research uses a completely randomized design which was factorially composed, consisting of 2 factors, namely (1) dosage of chicken manure (D), consists of 4 levels, (2) watering frequency (F), consists of 3 levels. From these two factors, were obtained   12 treatment combinations, where each of which was replicated 3 times. Data were analyzed by Analysis of variance, continued by Honestly Significant Diferent Test.  The results of this study is: (1) interaction between dosage of chicken manure and frequency of watering occurs only to seedling height, (2) the dosage of chicken manure significantly effected to stem diameter, number of compound leaves, fresh  weight of seedlings,  and dry  weight  of  seedlings.  While frequency of watering significantly effects only the stem diameter, (3) chicken manure with a dosage of 37.5 g/crop is optimum dosage, while watering with a frequency of 2 times a day is right frequency of watering, for the growth of sengon seedling.